Relation between students questions during practicum and the requirements for the graduated teacher (Revista Electrónica Diálogos Educativos. REDE, 2019)
The requirements and standards oriented to educational programs are present in Chile since 2011, which include the minimal knowledge and skills expected for the graduated students. However, the literature about the presence and development of these standards during the formative process is limited. The objective of the study is: to describe the relation between the questions originated by the reflexive process of the students during practicum and the requirements for the graduate teaching of high school.This research is descriptive and cross-sectional, which pursues to specify the present studied properties in a particular moment, through the process of data collection and descriptive data analysis, for the purpose of collecting reliable data in respect to the relation between the questions of the students and the requirements for the graduated teacher.The data was collected by the application of an on-line questionnaire, which consisted of two open questions, at the end of the process of practicum I, II and III, during the year 2015. This questionnaire was answered by 373 students of a high school teaching program.The results demonstrate a heterogeneous relation between the questions done by the students and the 10 requirements for the graduate teaching. Standars E5 and E10 being outstand for the high percentage. It is concluded that the students during their practicum pursue to answers to questions related to classroom management and the creation of an appropriate atmosphere for learning, which originate in the reflexive process, as a result of their progressive incorporation to the education system.